Genetic Characterization of Salmonella Typhimurium Isolates from Faeces of Children with Gastroenteritis Hospitalized in Baqiatollah-Azam Hospital, Tehran, Iran - Hamid Staji; Alfreda Tonelli; Taghi Zahraei Salehi; Mariangela Iorio; Federica Lopes (Pasteur Institute of Iran, 2015)
Introduction: In Iran, invasive nontyphoidal Salmonella (iNTS) disease causes severe bacteremic illness among children <5 years old. The global yearly incidence of iNTS disease in children was reported to be in the 3.4 (range  2.1-6.5) million cases,  (overall incidence 49 cases (range 30-94) per 100,000 population), the iNTS case-fatality ratio (CFR) of 20% yielded 681,316  deaths annually. Methods: The microarray analysis enables identification of the strains that have the 90kb Salmonella typhimurium virulence plasmid, presence or absence of the Salmonella pathogenicity islands (SPIs), adherence factors and other  virulence determinants. Twelve isolates of S. typhimurium obtained from faeces of children with gastroenteritis were analyzed  by microarray technique. Results: The virulence plasmid was present in 83.33% of isolates and all the isolates contained the  SPI-4 and SPI-5. None of the strains had the cytolethal distending toxin, cdtB. All strains were positive for rck and mig-14. The adherence genes were present in all the strains in the range of  51.55%  to 73.20% of the adherence genes interrogated in the  microarray. Two strains were the least pathogenic S. typhimurium. Conclusion: Microarray analysis proved to be a valuable tool in confirmation of serotyping results and genetic characterization of S. Typhimurium.